Electrolyte Gated Polymer Light‐Emitting Transistor. Issue 8 (13th September 2016) - Luan, Xinning; Liu, Jiang; Pei, Qibing; Bazan, Guillermo C.; Li, Huaping
Abstract : A first electrolyte gated polymer light‐emitting transistor (PLET) is reported with high performances up to 4000 cd m −2 brightness and 2.3% external quantum efficiency. This novel polymer electrolyte (PE) gated PLET is characterized and interpreted as reversible electrochemical doping of light‐emitting polymer under the assistance of PE at their interface, leading to current density and electroluminescence modulation by the applied gate potential.